HEDONISME DAN KRISIS ETIKA PENDIDIKAN: PERAN STRATEGIS PENDIDIK DALAM MEMBENTUK KARAKTER - Maulana, Rizki; Diniyah, Aurorah; Amelia Safitri, Nova; Rahmiati; Faqih Romadhon , Thorikul; Iryani, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the hedonistic lifestyle that is beginning to influence students and its impact on the decline of ethics in education. It also highlights the crucial role of educators in shaping the character of the younger generation amidst the rise of excessive lifestyles, declining student discipline, and a weakening enthusiasm for learning due to instant digitalization. The method used was a qualitative literature study approach, collecting data from relevant books, journals, and articles. First, the hedonistic lifestyle among students is influenced by social media and a consumer culture that makes momentary pleasures the measure of happiness. Second, this condition has an impact on the decline of ethics in the educational environment, such as a decrease in discipline, responsibility, honesty, and respect for teachers. Third, teachers still have a significant role as role models, guides, and shapers of moral values as long as character education is implemented effectively in learning. Overall, this study confirms that character education is a crucial solution to address moral decline in the modern era. Instilling the values of discipline, responsibility, hard work, and simplicity needs to be done consistently. Collaboration between schools, families, and the community is necessary for optimal character development in students. For further research, it is recommended to conduct field studies so that the results are more accurate and can be proven empirically in depth in the future.